Actual Performance Analysis of a Rankine Back Pressure System on a 1600 kW Turbine-Generator Unit at PT Kencana Sawit Indonesia Using Python Programming - Muhammad Bayu Septian; Arwizet K; Yolli Fernanda; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2026)
The Palm oil mills require steam systems that can supply electricity and process heat at the same time. This study analyzes the actual performance of a Rankine back pressure system on a 1600 kW turbine-generator unit at PT Kencana Sawit Indonesia using Python programming. The study used field documentation, equipment nameplate data, turbine-generator logsheet data, and an assumed steam flow scenario of 21.0-26.0 ton/h because the boiler steam flow indicator was reported to show an over-range condition. The analysis was carried out by converting actual operating data into thermodynamic performance parameters, including generator load, steam rate, turbine efficiency estimation, power-only efficiency, and energy utilization tendency. The results show that the unit operated under partial load with an average generator output of 715.19 kW or about 44.70% of the 1600 kW nominal capacity. The average steam rate increased from 32.99 kg/kWh at 21.0 ton/h to 40.85 kg/kWh at 26.0 ton/h. The estimated turbine efficiency decreased from 43.45% to 35.10% as the assumed steam flow increased. The power-only efficiency remained low because the exhaust steam was not discharged as waste heat, but was used as process steam in the back pressure system. Python-based processing provides a transparent and repeatable approach for evaluating field logsheet data.